Poruchy metabolismu fruktózy a infúze - Palyza, V; Bocková, M (Vnitrni lekarstvi, 1992)
The authors give an account of views regarding the use of non-glucose energy sources in parenteral nutrition during the immediate post-load period/serious operations, severe injuries). Attention is devoted to the metabolic pathway of fructose and its disorders. In hereditary fructose intolerance an infusion of D-fructose or D-glucitol (= sorbitol) can induce life threatening hypoglycaemia (unless glucose is administered concurrently). According to some views, in subjects with this intolerance the organism is threatened also by hepatic and renal failure; their development may be independent on hypoglycaemia. Fructose and D-glucitol (sorbitol) therefore should not be administered by the parenteral route. This view is supported by cases where hereditary fructose intolerance could not be revealed from the case-history and clinical manifestations. Some countries have already eliminated fructose and D-glucitol (sorbitol) from their pharmacopoeias.
Keywords: Food, Formulated; Sorbitol; Humans; potrava speciální; fruktosa; sorbitol; Fructose; Fructose Metabolism, Inborn Errors; Parenteral Nutrition; lidé; parenterální výživa; vrozené poruchy metabolismu fruktózy